PHYSIOTHERAPEUTIC APPROACH IN PAIN MANAGEMENT IN PRIMARY HEALTH CARE: AN EXPERIENCE REPORT (REMUNOM, 2025)
Objective: To report the physiotherapeutic role in pain management in a Primary Health Care Unit.Methods: This is a descriptive study, in the form of an experience report, resulting from a physiotherapy internship in a program called Pain Outpatient Clinic, a pioneering project of the Multiprofessional Residency in Family Health at the State University of Piauí, carried out in a Primary Health Care Unit in the municipality of Teresina – Piauí. The project consisted of specialized and individualized care for patients with chronic pain, rheumatologic diseases, and chronic musculoskeletal disorders. The supervised internship took place from August to December 2024, with two weekly sessions. Patients were referred to the physiotherapy outpatient clinic after spontaneous demand assessment by the multiprofessional residency team of the Primary Health Care Unit. In the clinic, a physiotherapeutic assessment was applied, subdivided into three processes: the first comprising a complete anamnesis, the second comprising the history of previous illnesses, and the third fully focused on pain analysis. Results: The Pain Outpatient Clinic brought an innovative perspective to physiotherapeutic care in Primary Health Care, with specialized and individualized sessions, and thus gradually managed to overcome some of the initial barriers encountered at the beginning of the project. Conclusion: It is concluded that the internship at the Pain Outpatient Clinic provided a unique experience of learning, knowledge exchange, and care for patients with chronic pain, contributing to improved quality of life and reduction of pain symptoms.